2018
DOI: 10.1016/j.taap.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

The asbestos-carbon nanotube analogy: An update

Abstract: Nanotechnology is an emerging industry based on commercialization of materials with one or more dimensions of 100 nm or less. Engineered nanomaterials are currently incorporated into thin films, porous materials, liquid suspensions, or filler/matrix nanocomposites with future applications predicted in energy and catalysis, microelectronics, environmental sensing and remediation, and nanomedicine. Carbon nanotubes are one-dimensional fibrous nanomaterials that physically resemble asbestos fibers. Toxicologic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 144 publications
2
62
0
3
Order By: Relevance
“…Similar biological outcomes were also observed after i.p. injection of long and rigid MWCNTs (Poland et al 2008 ), supporting the idea that these materials have asbestos-like pulmonary pathogenicity potential and should be regulated in the same way (Murphy et al 2011 ; Chernova et al 2017 ; Kane et al 2018 ). Using the same administration route, we have previously demonstrated that GO sheets of small lateral dimensions did not induce a granulomatous response (Ali-Boucetta et al 2013a ).…”
Section: Discussionmentioning
confidence: 80%
“…Similar biological outcomes were also observed after i.p. injection of long and rigid MWCNTs (Poland et al 2008 ), supporting the idea that these materials have asbestos-like pulmonary pathogenicity potential and should be regulated in the same way (Murphy et al 2011 ; Chernova et al 2017 ; Kane et al 2018 ). Using the same administration route, we have previously demonstrated that GO sheets of small lateral dimensions did not induce a granulomatous response (Ali-Boucetta et al 2013a ).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, MWCNTs were added into the culture, and inflammatory cytokines interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α in the culture solution were measured by enzyme-linked immunosorbent assay (ELISA). Neither MWCNTs nor tattoo ink increased the inflammatory cytokines in the culture [16]. CNTs have demonstrated favorable osteogenic responses in bone-related cells, and we believe that CNTs can be applied to orthopedic and dental implants and bone regeneration therapy.…”
Section: In Vitro Biocompatibility Testing Of Cntsmentioning
confidence: 88%
“…CNTs and asbestos often differ in their surface charge, hydrophilicity/hydrophobicity, active metal properties, tensile strength, and bio-durability. Despite these differences, the fibrous morphology of the nanoparticles has led some researchers to believe that CNTs may potentially be carcinogenic like asbestos [16]. The pharmacokinetics of these nanoparticles, as they are implanted in the body as biomaterials, remains unknown, and it is unclear how CNTs affect the living body.…”
Section: Introductionmentioning
confidence: 99%
“…The unique physicochemical properties of multi-walled carbon nanotubes (MWNTs) lend themselves to a variety of industrial and biomedical applications (for recent reviews, see [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]). However, there are environmental health and safety (EH&S) concerns associated with MWNTs because of consistent reports that they can be toxic (for recent reviews, see [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]). Moreover, anthropogenic MWNTs have been found in the lungs of asthmatic Parisian children not known to have been exposed to a source of MWNTs, suggesting that MWNTs may be a previously unrecognized air pollutant [ 23 ].…”
Section: Introductionmentioning
confidence: 99%